MONITORING TATA KELOLA DANA DESA TAHUN 2020 KECAMATAN PULUNG KABUPATEN PONOROGO - Sudarmanto, Sudarmanto (Master of Public Administration, Universitas Slamet Riyadi, 2021)
The birth of Law Number 6 of 2014 concerning Villages has placed the position of the village as a customary law community unit in accordance with the rights of the origin of the village, so that village autonomy is recognized and respected in the government system of the Unitary State of the Republic of Indonesia.Village Funds are funds sourced from the State Revenue and Expenditure Budget allocated to Villages which are transferred through the district / city Regional Revenue and Expenditure Budget and used to finance government administration, development implementation, community development, and empowerment. The purpose of this study was to determine how the effectiveness of the use of village funds for economic development and empowerment of rural communities in the Pulung district, Ponorogo district.This research is motivated by the existence of problems related to the governance of village funds. The level of budget absorption, but in terms of the accountability report, has not carried out village financial administration properly. On the basis of these problems, this study aims to analyze the implementation of village funds in 2020 in Pulung District, Regency. Monitoring theory in this study uses Dunn in (1981) that the implementation of village funds must be based on honesty and legal accountability, process accountability, program accountability and policy accountability.This study uses a descriptive method with a qualitative approach. Research informants using purposive sampling technique. Data collection techniques using in-depth interviews and documentation. The data analysis technique used is interactive analysis consisting of data collection, data condensation, data presentation and conclusion drawing.